Zone of tolerance for banks: a diagnostic model of service quality - Nadiri, Halil; Kandampully, Jay; Hussain, Kashif (Routledge Journals, Taylor & Francis Ltd, 2009)
Service quality has become an increasingly important factor for success and survival in the banking sector. Provision of high-quality service aids in meeting several requirements such as customer satisfaction and its consequent loyalty and market share, soliciting new customers, financial performance, and profitability (Cui, C.C., Lewis, B.R., Park, W. (2003). Service quality measurement in the banking sector in South Korea. International Journal of Bank Marketing, 21(4), 191-201.). This paper presents the bank service quality measurement in its extended form. It deals with the concept of 'zone of tolerance' in judgments of service quality proposed by Zeithaml, Berry, and Parasuraman (1993, The nature and determinants of customer expectations of service. Journal of the Academy of Marketing Science, 21(1), 1-12.). The 'zone of tolerance' is recognized in the service quality literature as representing a range of expectations and an area of acceptable outcomes in service interactions. The present study describes the zone of tolerance for young customers' service expectations and determines the customer satisfaction level for banks. The study focusses only on the youth market to formulate long-term strategies because young customers tend to keep themselves up to date with latest technological developments. A conceptual model BANKZOT is presented in this study, and the results demonstrate that evaluation of services can be scaled according to different types of expectations - 'desired' and 'adequate' - and that customers use these two types of expectations as a comparison standard in evaluating bank services. The findings reveal that young customers have a narrow zone of tolerance with regard to the services provided by the banks. The results with respect to gap analysis reveal that there was a shortfall in the service quality provided by the banks in the sample, with the largest gap being found in tangibles and empathy of service quality dimensions. The results of exploratory factor analysis reveal that the SERVQUAL model is found to be uni-dimensional in this study. The results, managerial implications, and future research implications are discussed in detail.
Keywords: service quality; customer satisfaction; zone of tolerance; banks; university students